THE INFLUENCE OF PHYSICOCHEMICAL PARAMETERS ON THE ABUNDANCE OF MACROZOOBENTHOS IN KUNGKILAN RIVER, SOUTH SUMATERA - Teristiandi, Novin; Yuliana, Meta (BRIN - Badan Riset dan Inovasi Nasional, 2025)
Macrozoobenthos are effective bioindicators for assessing freshwater ecosystem health. This study examines the influence of physicochemical parameters and spatial-temporal variation on macrozoobenthic abundance in the Kungkilan River, South Sumatera. Sampling was conducted at upstream, midstream, and downstream sites. Generalized Linear Mixed Model (GLMM) analysis revealed that water depth and transparency had significant positive effects, while iron (Fe) in sediment had a negative effect. Random effects analysis showed that site-level variability (variance = 0.680) was far greater than temporal variability, indicating that spatial differences—especially in the midstream zone—were the dominant drivers of community structure. These findings highlight the importance of localized conservation efforts and reinforce the role of macrozoobenthos as reliable indicators of river health in tropical ecosystems.